Structured Strategic Evaluation Model: Early Reading Skills Using A Reading Wheel Board - Mardiana; Suhawono; Yulianingsih (Jurnal Ilmiah Sekolah Dasar, 2025)
The persistent low reading proficiency among primary school students remains a critical concern, particularly because early reading skills serve as the foundation for long term literacy development and academic success. This study aims to analyze the effectiveness of integrating a structured strategy evaluation model with the use of a reading wheel board to enhance early reading abilities in children aged 6–7 years. The research employed an action research design conducted across multiple cycles, involving young learners as the primary participants. Data were collected through observations, interviews, documentation, and reading tests, while qualitative data analysis was conducted using NVivo 12 to identify learning patterns and developmental changes during the intervention process. The findings indicate consistent improvements in students’ reading abilities across cycles, with the interaction between the evaluation model and instructional media demonstrating an effectiveness rate of 91.7%. Additionally, final reading test outcomes reached 92.5%, providing strong evidence of the intervention’s success. The reading wheel board proved particularly effective in increasing student engagement, supporting phoneme recognition, and creating an interactive and enjoyable learning environment. These results suggest that the integration of interactive visual media with a structured strategy evaluation model can serve as an effective and sustainable pedagogical approach for strengthening early literacy skills in primary education.